The evaluation of the seismic performance of tall bridge piers with non-adaptive pushover methods. (February 2023) - Lu, Xingji; Li, Jianzhong
Abstract: The number of tall-pier bridges is increasing rapidly in the southwestern region of China, but the seismic behaviors of these special bridges have not been well understood. The present paper evaluates the effectiveness of two multi-mode non-adaptive pushover methods, including the energy-based MPA method and the direct vectorial addition (DVA) based pushover method in predicting the curvature ductility demands of four tall single-column piers. The four tall piers are designed to investigate two parameters including the pier height (60 m or 100 m) and the variation of cross-sections (constant or variable). The effectiveness of each pushover method is evaluated by comparing the curvature ductility demands obtained from pushover analyses with those obtained from incremental dynamic analyses (IDAs), during which both far-field and near-field earthquake records are considered, and the peak ground acceleration (PGA) is employed as the intensity measure of the records. High curvature ductility demands are observed at both bottom and mid-height regions in all tall piers. However, in the piers with variable cross-sections, the demands at the mid-height region are even greater than those at the bottom region. For each tall pier, the location of the maximum curvature ductility demand at the mid-height region is determined based on the parametric study. The comparative evaluations indicate the DVA-based pushover method is capable of predicting the curvature ductility demands at both the mid-height and the bottom regions of the tall piers.